Optimalisasi Pengelolaan Kesehatan Dan Keselamatan Kerja (K3) Pada Bidang Pengawasan Kearsipan Melalui Komunikasi Efektif - Marescotti, Katharina Giacinta; Retu, Markus Kristian; Sedu, Viktor Ariestyan (CV. ITTC INDONESIA, 2024)
A variety of policies at the tertiary level are applied to the management and safety of work, particularly within the field of archives. The Sikka Regency Regional Archives and Library Office is a local government institution with the responsibility of managing archives and developing libraries within the Sikka Regency area. One indicator of governmental management is that awareness of the importance of archives is often still low. This can result in disorganization in archive management, which can in turn lead to the loss of important data, difficulty in finding information, and increased risk of errors in decision-making. Many employees have not yet fully recognized the importance of archiving, which has resulted in a lack of organization in the filing system. Therefore, it is necessary to optimize archival supervision in order to establish a more orderly and systematic archive management system. One strategy that can be employed in optimizing archival supervision is to conduct effective communication. Effective communication is a critical factor in ensuring workplace safety and health. The implementation of the Occupational Safety and Health Management System, Article 13 emphasizes the importance of communicating OSH-related information to all parties, both within and outside the organization. Effective communication can be defined as the process of delivering information in a clear, precise manner that can be understood by all parties involved. The objective of this research is to enhance the efficacy of communication pertaining to archive management among the various stakeholders within the organization. The research methodology employed is a qualitative approach, wherein data is gathered through observation, interviews, questionnaires, and document analysis. This research examines the processes of effective supervision and communication at the Sikka Regency Regional Archives and Library Office, with the aim of increasing awareness among all parties (employees and management) about the significance of archives and archival order within the organization.